2010
DOI: 10.1016/j.ijdevneu.2010.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of sleep patterns in healthy Japanese 5‐year‐old children

Abstract: Our current findings suggested that both intrinsic and extrinsic factors, such as gender, child care, lifestyle and after-nursery lessons, influence the establishment of sleep patterns in young preschool children. Further investigation of these independent variables may help establish a strategy for predicting and preventing sleep disorders later in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 32 publications
1
36
0
1
Order By: Relevance
“…Table 3 provides a summary of the magnitude of findings and documents a moderate association of napping with night sleep patterns including later sleep onset,15 18 19 reduced duration5 16 17 20 and quality indices 16 19 20. Three studies examine differences in total 24 h sleep duration and report no difference between those who do and do not nap, indicating that daytime napping changes the distribution, rather than the duration, of sleep in a 24 h period 5 16 20.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 provides a summary of the magnitude of findings and documents a moderate association of napping with night sleep patterns including later sleep onset,15 18 19 reduced duration5 16 17 20 and quality indices 16 19 20. Three studies examine differences in total 24 h sleep duration and report no difference between those who do and do not nap, indicating that daytime napping changes the distribution, rather than the duration, of sleep in a 24 h period 5 16 20.…”
Section: Resultsmentioning
confidence: 99%
“…Sleep duration at night increased with age as a result of decreasing daytime sleep duration in 1 year old children. 7 Studies from different countries and different age groups reported the night-time sleep duration as 7.7±1.3 to 11.7±1.0 hours. 9,11,13,14,33 Behaviours such as breastfeeding, sleeping in the same room and the same bed with parents or siblings, bottle-feeding when the child wakes up at night, and bringing the child to the parents' bed reduce sleep duration.…”
Section: Discussionmentioning
confidence: 98%
“…1,5 Sleep problems may persist if not adequately managed and may lead to health issues in children such as obesity, insulin resistance, cardiovascular/immune system disorders, anxiety, and depression. 1,6,7 The most common way of obtaining information about the sleep habits of children is through observation of the families. [8][9][10] Identifying sleep characteristics such as the duration of sleep and bedtime/daytime sleep habits is very important in understanding sleep-related problems.…”
mentioning
confidence: 99%
“…Gece boyunca yatak ıslatmaya bağlı olan uyanmaların çocukların gece uykusunda kesintilere yol açtığını, etkin uyku uyuyamamalarına bağlı olarak da gün içinde kısa süreli şekerlemeler yaşadıklarını düşünmekteyiz. Bir diğer önemli nokta ise "parçalanma indeksi" olarak tanımlanan uykunun kesintiye uğramasıdır (23,25). Uyku ve yaşam kalitesi üzerine olumsuz etkisi olan çocukluk çağının önemli hastalıkları olan alerjik rinit ve astımlı çocukların uyku kalitesi aktigrafi ile değerlendirilmiş ve "parçalanma indeksi"nde etkilenim olduğu, uyku kalitesinin bu hastalıklarda bozulduğu bulunmuştur (26).…”
Section: Bulgularunclassified